CITOGENÉTICA COMPARADA EM PEIXES DO GÊNERO Cheirodon (OSTARIOPHYSI: CHARACIDAE), COM FOCO EM ESPÉCIES TRANSANDINAS - Ortiz, Miguel ángel Soto (2017)
Within the great biodiversity of freshwater fish of South America, the Characidae family has been one of the most controversial groups taxonomically. In the trans-Andean country of Chile, the family is represented only by the Cheirodontinae of the genus Cheirodon and its five species, of which C. pisciculus, C. galusdae, C. kiliani and C. australe are endemic, and C. interruptus is native to the Atlantic basins of Argentina, Uruguay and Brazil. In order to contribute to the description of the evolutionary relationships and taxonomic delimitation of the species of genus Cheirodon present in Chile, the karyotypes of these five species are described for the first time and compared by their diploid number, chromosomic morphology, C bands, Nucleolar Organizer Regions (Ag-NOR) and the rDNA 5S and 18S marking by fluorescence in situ hybridization (FISH). For all the analyzed species the diploid number was 50 chromosomes, varying in the karyotype formula among the metacentric, submetacentric, subtelocentric and acrocentric types. The number of chromosome arms was 68 in C. australe and C. kiliani and 66 in C. galusdae, C. pisciculus and C. interruptus. The presence and distribution of constitutive heterochromatin was similar in the five species, being observed mainly in the centromeres and telomeres. Variation in the number and distribution of the 5S and 18S rDNA regions was observed, being those two clusters on different chromosomes or in syntenia. It was also observed a variation in the activity of RONs, being found in C. kiliani and C. galusdae, the highest level of relative activity. There is a greater karyotype similarity between the two species that living more to the south in relation to those with the most central and north distribution, evidencing a reflection of hydrograph formation and species isolation.